A prototype of indoor hydropnics farming framework - Lee, Song Yao (2021)
This project is an indoor hydroponic farming framework for academic purpose. It works by using a single board computer as the main controller to command and receive data from sensors and actuators. The indoor hydroponic farming framework contains the main controller, sensors, and actuators which will help to maintain the health of the crops within the entire life cycle until the time to harvest. The data collected will be publish to the cloud service provider dashboard for storage purpose and to display in real-time to the user while a camera is placed within the farming framework which will stream the live feed of the farm into a streaming platform then embedded into the cloud service provider dashboard for live viewing of the farm at any location. The indoor hydroponic farming framework also being developed in an isolated environment which will attempt to reduce dependencies to the weather differ to the major traditional soilbased farming which is highly dependent on the weather. With the sensors, actuators, and the camera being placed, the indoor hydroponic farming framework aims to be having least human interaction as possible when the crops are growing until the time of harvest. In short, this project proposed an indoor hydroponic farming framework which is developed to be less dependent on weather by isolating from the outdoor environment, real-time monitoring of farming framework status by reading data from sensors then transmit through MQTT protocol with live feed of the farm embedded at the same SaaS cloud service dashboard.